68Maternal exposure to PM2.5 from a severe smoke event and birth outcomes in Victoria, Australia. (2nd September 2021) - Melody, Shannon; Wills, Karen; Ford, Jane; Venn, Alison; Johnston, Fay
Abstract: Background: The 2014 Hazelwood coal mine fire was an unprecedented six-week severe smoke event in the Latrobe Valley, southeastern Australia. We aimed to determine whether maternal exposure to fine particulate matter (PM2.5 ) attributable to the event was associated with adverse fetal growth or maturity, including birthweight, small for gestational age, term low birthweight or preterm birth. Methods: A cohort of babies born within the affected region was defined used administrative perinatal data. Maternal average and peak PM2.5 was assigned to residential address at time of delivery using a chemical transport model. Maternal, infant, meteorological and temporal variables were included in final linear and log-binomial regression models. Results: 3, 591 singleton livebirths were included; 763 were exposed in utero . Average PM2.5 exposure was 4.4 µg/m 3 (IQR 2.1 µg/m 3 ); average peak was 45.0 µg/m 3 (IQR 35.1 µg/m 3 ). No association between PM2.5 and fetal growth or maturity was observed. Gestational diabetes mellitus was an effect modifier in the relationship; babies of exposed gestational diabetic mothers were 97 grams heavier per 10 µg/m 3 increase in average PM2.5 exposure (95%CI 74, 120 grams), compared to mothers without gestational diabetes. Conclusions: Maternal PM2.5 exposure from a smoke event was not associated with adverse fetal growth or maturity. There was a trophic response amongst babies of mothers with gestational diabetes. Key messages: Babies born to mothers with gestational diabetes may be more susceptible to the effects of smoke events on birthweight.